Pengaruh Metode Self Direct Video dan Simulasi Terhadap Pengetahuan dan Keterampilan Resusitasi Jantung Paru (RJP) pada Relawan - Indri Wahyuningsih; Vita Amilia Rifa’i; Risa Herlianita; Indah Dwi Pratiwi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Out-of-hospital cardiac arrest (OHCA) victims, >40% were handled by non-professionals who performed less than optimal CPR. To improve the knowledge and skills of helpers, namely providing education through self-directed videos and simulations. Objectives: To identify knowledge and skills in the management of cardiac arrest using self-direct video methods and simulations of Cardiopulmonary Resuscitation (CPR) on Volunteers. Methods: This type of research is an experiment using a one-group prepost-test. The sample is 15 respondents with purposive sampling technique. Collecting data using questionnaires and observation sheets. Results: There was a significant difference in knowledge (Sig. 0.004) and there was no significant difference in CPR skills in adult and infant victims (0.083).